Negative Politeness Strategies in “Big Hero 6” Movie - Adrian Kurniandi Makasiahe; Melly Siska Suryani (Institut Agama Islam Negeri Palopo, 2020)
This article describes the study of pragmatics that analyzes about the negative politeness strategies. The aim of this study is to find out the type of negative politeness strategies in movie “Big Hero 6”. The theory used is Levinson (2009). In this research, the researcher applied the qualitative descriptive method. The method of collecting data is observation. The researcher found 20 data that contain negative politeness strategies, the using of be indirect is 1 data, the using of question or hedging is 7 data, the using of minimize imposition 4 data, the using apologize 3 data, the using of give deference 1 data, and the using of plural pronoun is 4 data.